Peranan Kesenian Adok Sebagai Sarana Pendidikan Estetika Pada Masyarakat di Korong Ubun-Ubun - Selvi Kasman; Fahmi Marh; Saaduddin Saaduddin (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2020)
This paper aims to reveal the aesthetic values and ideas contained in the musical art of Adok in Korong Ubun-Ubun, which acts as a means of aesthetic education for the performing arts community and the supporting community. As a virtue contained in Adok art, the aesthetic values and ideas make the position of Adok art different when compared to other traditional arts, so that the research is important. The research location was Jorong Ujuang Ladang, Korong Ubun-Ubun, Kanagarian X Koto Singkarak, Solok Regency. The object of research was Art Adok, focusing on the aesthetic aspects of the performance. This study uses an ethnographic approach and data collection techniques through participant observation. Minang values related to the value of taste (aesthetics) in Adok art contribute positively to the perspective of the supporting community so that they can change people’s perceptions and understanding of Adok art. The results of this study can also prove that the Adok art can be one of the presentations of Minang’s which the supporting community has not realized.